2021
DOI: 10.9734/ijtdh/2021/v42i530453
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Delay in Healthcare Seeking for Common Childhood Illnesses among Caregivers with Under-Five Children in Touboro Health District, Near Cameroon’ s Northeastern Border with Chad

Abstract: Aims: The study sought to determine the determinants of delay in health-seeking among caregivers with under-five children. Study Design: This was a mixed-method, cross-sectional study. Place and Duration of Study: The study took place in Touboro Health District involving 386 caregivers of under-five children from May to July 30, 2020. Methodology: A structured questionnaire and two focused group discussions were used to gather information on caregiver knowledge of healthcare-seeking behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…The proportion of delayed healthcare seeking in current study is also lower than a study conducted in Cameroon, which reported a proportion of 88.1% ( 28 ). This disparity could be attributed to differences in the timing of the studies.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…The proportion of delayed healthcare seeking in current study is also lower than a study conducted in Cameroon, which reported a proportion of 88.1% ( 28 ). This disparity could be attributed to differences in the timing of the studies.…”
Section: Discussioncontrasting
confidence: 89%
“…The questionnaire was developed by reviewing relevant literature (19,28,33,34). A structured interview administered questionnaire was employed to collect the data.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations